If it's not what You are looking for type in the equation solver your own equation and let us solve it.
37-2(c+3)=4(c+5)+c
We simplify the equation to the form, which is simple to understand
37-2(c+3)=4(c+5)+c
Reorder the terms in parentheses
37+(-2c-6)=4*(c+5)+c
Remove unnecessary parentheses
+37-2c-6=+4+*(+c+5+)+c
Reorder the terms in parentheses
37-2c-6=+(+4c+20)+c
Remove unnecessary parentheses
+37-2c-6=+4c+20+c
We move all terms containing c to the left and all other terms to the right.
-2c-4c-1c=+20-37+6
We simplify left and right side of the equation.
-7c=-11
We divide both sides of the equation by -7 to get c.
c=1.57142857143
| 57*3=2x | | 18x+7(5x-9)+5(2x+7)+9=2x+5 | | -x-5=2x-5 | | 11+x=-19 | | 6(5p-2)=138 | | x+-44=-81 | | 98(-3)+98(3)=y | | -2w+8=-4w | | x+9x+4=0 | | 2+4lnx=12 | | 4x-2+5x+4=2x-3x+3-4 | | 5.2k=3.7+12.9 | | n+1=n | | -13+-5x=-43 | | -46+x=-72 | | 9x^2+22x-49-13x^2-8x+15= | | 12x+4=9+4x | | 9=2a+7 | | 6ln(7x)=13 | | -46+x=72 | | 2m^2-25m-90=0 | | p-4=-9+x | | 3(y+2)-2y=1 | | 3-x-x=-19 | | 42+x=65 | | 43=6x+1 | | 25x-40=0 | | 5x^2-3x-80=0 | | x+y+57=180 | | -2(3+6m)=-66 | | 31=6x+1 | | -5.00+-4.00x=-53.00 |